Intra and inter-tester reliability of a novel device to assess gluteal muscle strength in professional football players - Moreno-Pérez, V.; Beato, M.; Del Coso, J.; Hernández-Davó, J. L., Soler, A.; Peñaranda-Moraga, M.; Madruga-Parera, M.; Romero-Rodríguez, D. (Research in Sports Medicine, 2022)
The aim of this study is to investigate inter-tester and intra-tester reliability of a novel clam test (CLAMT) for the measurement of gluteal muscle strength and to detect possible differences between CLAMT values in football players with and without a history of groin injuries. Twenty male football players participated in the test-retest and sixty-two male professional football players participated in the case-control study. Hip abductor maximal muscle strength was evaluated either using CLAMT or in a supine position with the hip in a neutral pose. For CLAMT, intraclass correlation coefficient (ICC) for inter-tester-intra-day reliability was 0.80 (95% CI: 0.60-0.90), with a standard error of measurement of 34.2N. The intra-tester-intra-day ICC was 0.92 (95% CI: 0.87-0.95), with a standard error of measurement of 23.6N. The inter-week ICC was 0.96 (95% CI: 0.92-0.98), with a standard error of measurement of 18.9N. CLAMT showed lower (but not significant) strength values in football players with a history of groin injuries to non-injured players. CLAMT showed good to excellent levels of reliability, intraday and inter-week, with low standard errors of measurement while it was effective (possible) to identify residual weakness in players with previous groin injuries.